FOSTERING HIGH SCHOOL ENGLISH AS A FOREIGN LANGUAGE (EFL) STUDENTS’ SPEAKING CONFIDENCE THROUGH PHOTOVOICE 2.0: A QUALITATIVE CASE STUDY - Chabibah, Faricha Maula; Pratama, Hendi (Premise: Journal of English Education and Applied Linguistics, 2026)
This study explores the implementation, impact, and students' perceptions of Photovoice 2.0 in fostering speaking skills. Employing a qualitative case study design, it involved eight purposively selected high school students at SMA Negeri 7 Semarang. Data were gathered through digital observations, semi-structured interviews, and qualitative analysis of voice notes using a validated rubric. The data analysis involved thematic analysis and triangulation to ensure the credibility of the findings. The results indicated that Photovoice 2.0 empowered students as co-researchers and showed strong potential in reducing speaking anxiety. Based on the qualitative speaking rubric, students achieved a high average score of 4.56 out of 5.0, with Comprehensibility and Content & SHOWED Analysis receiving the highest marks (4.75). The Vocabulary aspect recorded the lowest score (4.25), suggesting a need for more explicit linguistic support. Overall, students perceived the method positively, noting increased motivation, confidence, and material relevance. This study concludes that Photovoice 2.0 serves as a strong pedagogical strategy that develops both oral proficiency and critical thinking within digital learning environments. Furthermore, the study implies that integrating Photovoice 2.0 serves as a transformative pedagogical tool for EFL teachers to foster a more inclusive speaking environment and effectively mitigate students' speaking anxiety.